Explaining a Model of Applying Critical Thinking Components in High School Curriculum Development: A Qualitative Approach - Hossein Ali Fatehi; Farzaneh Vasefian; Malihe Arabhashemi (Iranian Evolutionary Educational Psychology Journal, 2022)
The main purpose of this study is to study the components of critical thinking and the extent to which it is used in the development of the curriculum of the first level of high school in order to provide an appropriate model. The present study is applied in terms of purpose and qualitative in terms of method. The statistical population was university professors, teachers and curriculum experts in education in Kohgiluyeh and Boyer-Ahmad province (Iran). Using purposive sampling method (theoretical saturation - key people selection approach), eleven of them were selected. The semi-structured interviews were used for data collection and data analysis was done via thematic analysis. According to findings, using of components (skills) of critical thinking in curriculum development as an inclusive theme (4 sub-thematic themes), 6 organizing themes and 121 basic themes were identified and a network of themes was extracted. The organizing themes include extracurricular-based curriculum, evaluation, interpretation, analysis, self-regulation, and synthesis. The alignment of the components and themes of the drawn theme network with theoretical and research bases was examined and approved.